แนวทางการออกแบบอาคารโฮมมาร์ทสีเขียวให้สอดคล้องกับเกณฑ์ประสิทธิภาพพลังงานของ LEED - อุราวัลย์ รุกขไชยศิริกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
To study the energy performance of the SCG HOME MART store building, a retail outlet for construction materials owned by SCG DISTRIBUTION under SCG Groups. The problem is that SCG HOME MART stores are designed without due consideration for energy performance, and lack any OTTV, RTTV calculation. They are operational during daytime more than nighttime and constantly need to adjust the ambient environment to support the buildings various usage behaviors. The surrounding environment of the building includes thermal conductivity factors into the building such as material product pile, truck, fork lift, crane, pallet, office equipments etc. In addition, the management of the building’s occupants has not been considered in terms of energy efficiency. As a result, energy consumption is clearly increasing. The aim of the research was to create design guidelines for a SCG HOME MART prototype store which takes into consideration energy efficiency and values that are consistent with international green building energy efficiency criteria such as LEED (Leadership in Energy and Environmental Design) by US Green Building Council. The research stages proceeded as follows: 1.Educational research and theories. 2.Survey collected information on energy consumption of building case study SCG HOME MART store. Simulating energy using Visual Doe4.1, a database for SCG Base line. 3.Simulation of building energy Basis ASHRAE 90.1 2007 with Visual Doe4.1 and compare and improve the design of SCG NEW 1 and SCG NEW 2 in order to reduce power consumption by 12% from the criteria of ASHRAE 90.1 2007. 4.Analysis of economic value. Summary of results. To present recommendations, including guidelines for the building in the same category. Technical analysis shows that the SCG HOME MART stores have met energy-saving criteria of green buildings in Thailand already. However, due to the fact that SCG intend to accord with the stricter criteria of LEED, they have invested more in building improvement, especially the selection of good quality envelope materials that can reduce power consumption by up to 12.7% at 153,888 baht per year. Construction costs increased 1,498,011.75 baht and a return on investment (ROI) can be achieved within 10.45 years. Additional expenses to adjust the lighting system can save energy up to 31.04% at 375,084 baht, with an ROI of 6.93 years.